Ministry of Communications and Digital Economy | Home - Ministry of Communications and Digital Economy (Nigeria) (2020)
Ministry of Communications and Digital Economy, MCT, MOC, FMOC, FMCDE, FMOCDE, MCDE, MOCDE, Federal Ministry of Communications and Digital Economy
Library Catalog: www.commtech.gov.ng EdTechHub.ItemAlsoKnownAs: 2405685:YT9YM6T3

National Artificial Intelligence Strategy - Federal Ministry of Communications, Innovation and Digital Economy (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:PB4MH6T7 2405685:G5ZG7T9Z

Ministry’s Artificial Intelligence Strategy Workshop to Attract 120 Experts from Across the World - Federal Ministry of Communications, Innovation and Digital Economy (2024)
KerkoCite.ItemAlsoKnownAs: 2339240:TP2SEDX4 2405685:N8H96K5P